Cultivation of Religious Moderation Values in Students through Religious Education: Penanaman Nilai-Nilai Moderasi Beragama pada Peserta Didik melalui Pendidikan Agama - Yulianingsih, Wahyu Feby; Dartim, Dartim (Universitas Muhammadiyah Sidoarjo, 2025)
Religious moderation is a critical value in maintaining social harmony within Indonesia’s pluralistic society. In educational contexts, particularly in junior high schools, Islamic Religious Education (PAI) plays a strategic role in instilling values such as tolerance, anti-radicalism, and respect for diversity. However, limited empirical studies have investigated how these values are concretely embedded in formal education, especially in non-pesantren, public schools in rural settings. This study aims to explore the strategies employed by PAI teachers at SMP Negeri 2 Ngadirojo in fostering religious moderation, the dominant values emphasized, and the supporting and inhibiting factors. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation. The results show that the values of moderation are taught through curriculum integration, exemplary teacher behavior, daily habituation, and inclusive religious practices. Despite these efforts, challenges arise from limited teacher training and external influences such as intolerant social media content. The novelty of this study lies in its focus on a rural public school context, highlighting local cultural dynamics as a key enabler of contextualized religious moderation. The findings imply that PAI learning, when supported by reflective pedagogy and cultural sensitivity, can serve as a powerful medium for building a tolerant and cohesive young generation.Highlight : Religious moderation is taught through Islamic Education (PAI) by integrating values of tolerance, justice, and anti-radicalism. Teacher role modeling and inclusive school culture strengthen students' moderate religious attitudes. Challenges include limited curriculum integration, lack of teacher training, and external radical influences. Keywords : Religious Moderation, Islamic Religious Education, Junior High School Students, Tolerance, Religious Values